The characteristics of points of strong summability of the Fourier - Laplace series for functions from the class L(S^m) in the case of critical indicator - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We announce the result that enables one to determine fairly constructive characteristics of a set of points of full measure on a sphere L(S^m) at which the strong means converge to a given function f(·).